The Influence of Banjar Culture-Based Ethnopedagogical IPAS Learning Resources on Elementary Students’ Engagement in Differentiated Instruction - Wahyudi Rakhman; Bambang Subiyakto; Syaharuddin; Mutiani; Ersis Warmansyah Abbas (AR-RIAYAH: Jurnal Pendidikan Dasar, 2025)
Student engagement in differentiated instruction at SDN Berangas Barat 2 remains suboptimal. This is evident form students’ low levels of comprehension, collaboration intensity, discipline, ability to express opinions, and sustained focus during learning activities. One of the main contributing factors is the limited use of culturally relevant learning resources. Ethnopedagogy, as a pedagogical approach, is believed to transform cultural knowledge into meaningful learning resources. This study aims to examine the influence of Banjar culture-based ethnopedagogical IPAS learning resources on elementary students’ engagement in differentiated instruction. Employing a quasi-experimental method with a control group design, the study involved 46 sixth-grade students from SDN Berangas Barat 2, 23 students in Class VI A (experimental group) and 23 students in Class VI B (control group). Student engagement was measured using an observation instrument, and the collected data were analyzed using SPSS version 27, applying a two-tailed significance test with a threshold of <0,05. The results showed a Sig (2-tailed) value of <0,05. The results showed a Sig. (2-tailed) valued of <0.001. It is therefore concluded that the use of Banjar culture-based ethnopedagogical learning resources significantly enhances student’s engagement in differentiated instruction at the elementary school level.